Determinants of Poverty among Farming Households in Kogi State of Nigeria - Omonona, Bolarin T.; Okunmadewa, Foluso Y. (2012)
The dearth of studies on quantitative determinants of poverty in Nigeria is a major weak point in the country's poverty reduction policy and strategy formulation. A recent study in Kogi State of Nigeria revealed that poverty is higher among households that have male heads, are polygamous, have farming as the only occupation, have no formal education, and have no access to extension services and improved farming inputs. Poverty rises with the increase in household size and dependency ratio. On the other hand, poverty is inversely related to the extent of output commercialization, farm size, and credit. The study indicates that in Kogi State, Nigeria there is the need to reduce birth rate, provide training and education, and improve farming inputs, credit to deserving households, and marketing infrastructures, as major elements of an effective poverty reduction strategy.